2021
DOI: 10.1590/s1677-5538.ibju.2020.0959
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic predictors of lymph node metastasis in penile cancer: a systematic review

Abstract: Purpose: Squamous cell carcinoma (SCC) of the penis is a rare disease in developed countries but is associated with signifi cant morbidity and mortality. A crucial prognostic factor is the presence of inguinal lymph node metastases (ILNM) at the time of diagnosis. At least 25% of cases have micrometastases at the time of diagnosis. Therefore, we performed a literature review of studies evaluating factors, both clinical and pathological, predictive of lymph node metastases in penile SCC. Materials and methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 49 publications
(44 reference statements)
2
16
0
Order By: Relevance
“…On evaluating the National Cancer Database, Winters et al [13] found LVI as the strongest independent predictor of occult lymph node metastasis. A similar suggestion has been made by other authors also [14,15]. Grade and presence of LVI have also been included in the EAU risk stratification for clinically node negative disease.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…On evaluating the National Cancer Database, Winters et al [13] found LVI as the strongest independent predictor of occult lymph node metastasis. A similar suggestion has been made by other authors also [14,15]. Grade and presence of LVI have also been included in the EAU risk stratification for clinically node negative disease.…”
Section: Discussionmentioning
confidence: 54%
“…Advanced tumor stage and infiltrating pattern of invasion showed trend toward poorer prognosis, but were not significant on univariate analysis. Various authors have studied other molecular and biochemical markers, like p53, DNA binding protein inhibitor-1, superoxide dismutase 2 and squamous cell carcinoma antigen overexpression, matrix metalloproteinase-9, high e-cadherin, higher neutrophil to lymphocyte ratio, diffuse PD-L1 expression, and C-reactive protein >20, but further validation studies are required before incorporating them to clinical practice [15, 27, 28]. Our study is limited by its retrospective nature, small sample size and patients being treated at different time periods during which the understanding of the disease changed considerably leading to use of different modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Both drugs caused a pronounced downregulation of “inhibitor of DNA Binding/Inhibitor of differentiation” (ID) transcripts for ID1, ID3, and ID4, with GM-4-53 having more significant effects than paclitaxel. IDs are implicated in the control of cell division and mitosis not only during embryonic development but also in numerous cancers, including TNBC, being linked to larger tumor size, advanced histological grade, metastasis, vascular invasion, stem cell phenotype, lymph node invasion, and poor clinical outcomes [ 53 , 54 ]. The ID genes may control cell division by the indirect regulation of processes involving CDKN1A (p21) and CDKN1B (p27) [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we suggest that when considering lymph node dissection strategies for patients with higher stages, the primary conditions of patients should also be considered to avoid complications as far as possible. At present, many valuable studies have been published on whether LND should be performed (31)(32)(33). We should make full use of existing tools to evaluate whether LND is needed.…”
Section: Discussionmentioning
confidence: 99%